Enhancing Multi-Factor Authentication in Modern Computing - Iwuoha, Obioha2; Emmanuel, Nwabueze1; Ekwonwune, Emmanuel (My University, 2017)
Most network service providers like MTN Nigeria, currently use two-factor authentication for their 4G wireless networks. This exposes the network subscribers to identify theft and users data to security threats like snooping, sniffing, spoofing and phishing. There is need to curb these problems with the use of an enhanced multi-factor authentication approach. The objective of this work is to create a multi-factor authentication software for a 4G wireless network. Multi-factor authentication involves user’s knowledge factor, user’s possession factor and user’s inherence factor; that is who the user is to be presented before system access can be granted. The research methodologies used for this work include Structured System Analysis and Design Methodology, SSADM and Prototyping. The result of this work will be a Multi-factor authentications software. This software was designed with programming languages like ASP. NET, C# and Microsoft SQL Server for the database.
Keywords: Tokens; Malware; Phishing; Hackers; Encryption; Security Threat